EDUKASI ETIKA BERBAHASA PADA ANAK UNTUK MENCEGAH PERILAKU VERBAL NEGATIF AKIBAT GADGET DAN LINGKUNGAN - Rofiah, Zaimatur; Kholiq, Abdul (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2025)
This study is situated within the discourse of educational communication and character development, focusing on children’s language ethics in social and digital contexts. The rapid advancement of technology has transformed communication patterns among children, where the use of harsh expressions such as “jancok,” “endasmu,” “anjay,” and “anjir” has become increasingly common due to environmental influences and uncontrolled gadget exposure. This community engagement article aims to provide ethical language education for children in Warulor Village, Paciran District, Lamongan Regency, and to analyze the impact of this program on their verbal behavior. The study employed an educative-participatory approach, actively involving children through language games, conversational simulations, and reflective activities. Data were collected through observation, short interviews with teachers and parents, and simple pre- and post-tests assessing language ethics comprehension. The results revealed significant improvement in both knowledge and behavior—harsh language use decreased by up to 70%, and children began to internalize polite communication habits in social contexts. These findings highlight that participatory, community-based language ethics education can serve as an effective preventive strategy against negative verbal behavior in children. The study contributes to the field of communication and education by reinforcing the concept of character-based communication that integrates linguistic, social, and moral dimensions. Practically, it emphasizes the importance of collaboration among schools, families, and communities in fostering a polite and ethical language culture in the digital era.